The Gut Microbiome in Patients with Intestinal Failure: Current Evidence and Implications for Clinical Practice. Issue 2 (2nd August 2018) - Neelis, Esther; de Koning, Barbara; Rings, Edmond; Wijnen, René; Nichols, Ben; Hulst, Jessie; Gerasimidis, Konstantinos
Abstract: Intestinal failure (IF) is the reduction of gut function or mass below a minimum needed to absorb nutrients and fluids, such that patients are dependent on parenteral nutrition (PN). Patients with IF have an altered gut microbiome. Our aim was to review and evaluate the current evidence on gut microbiome and its metabolic activity, as well as its association with disease characteristics in adults and children with IF. We performed a PubMed literature search for articles published after 2000 using the following terms: intestinal, microbiome, microbiota, short‐chain fatty acids, short bowel syndrome, and PN. Literature search was restricted to human studies only. The gut microbiome diversity is remarkably reduced, and community structure is altered with a noticeable overabundance of Proteobacteria, especially the Enterobacteriaceae family. A substantial increase in Lactobacillus level is often reported in patients with IF. Gut microbiome characteristics have been associated with poor growth, liver disease, D‐lactic acidosis, and duration of intestinal adaptation. Differences in microbiome characteristics have been found between patients receiving PN and those whose guts have adapted and have been weaned off PN. Future research with prospective sample collection should explore the value of the gut microbiome as a biomarker to guide clinical practice and as a modifiable therapeutic target to optimize outcomes of patients with IF.